What happens to soil fumigants after nematode control? - I Thomason; C Castro; R Baines; R Mankau (California Agriculture, 1971)
The results of research on nematicides, in addition to demonstrating remarkable yield increases of agricultural crops brought about by nematpde control, have also shown that EDB, DBCP and 1,3-D have no significant persistent adverse effects on the physical and biological composition of soil, or on the nutritional value of crops grown on treated soil. These successful nematicides are physically and/or biologically degradable.